Pengaruh Firm Size, Likuiditas, Profitabilitas Dan Leverage Terhadap Manajemen Laba Pada Perusahaan Sub Sektor Perusahaan Efek Jasa Yang Terdaftar Di BEI Periode 2016-2020 - Muhammad Adji Purnomo; Emi Masyitah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Earnings management is the manager's decision to choose certain accounting policies that are considered to be able to achieve the desired goals. This study aims to examine the effect of profitability, leverage, liquidity, and firm size on earnings management in manufacturing companies. The variables used in the test are profitability, leverage, liquidity, and firm size as independent variables, and earnings management as the dependent variable. This research is a quantitative research. The source of this research data is secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange website. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The method of determining the sample used is the purposive sampling method. After being selected based on the purposive sampling method, there were a total sample of 45 samples with an observation period of 5 years. Hypothesis testing in this study using multiple linear regression analysis method using statistical application Statistical Package for Social Sciences (SPSS) version 22 as a test tool. The analytical methods used include descriptive statistical tests, classical assumption tests (test normality, multicollinearity, heteroscedasticity tests), and hypothesis testing.